Developing family-friendly signage in a South African paediatric healthcare setting - Angela L. Leonard; Anchen Verster; Minette Coetzee (AOSIS, 2014)
Background: Multiple renovations and changing flow in a tertiary children's hospital in Cape Town resulted in numerous signs being posted in the corridors and units, making wayfinding extremely complex. A request from nursing management prompted the formation of a learning collaborative of nurses from all departments to improve wayfinding signage. Objectives: The project aimed to contribute to a family-friendly environment by reviewing the current situation and developing signage to improve wayfinding and convey essential information to parents, caregivers and patients. Methods: A participative action research method followed a four-stage process to facilitate the development of family-friendly signage. Nurse participants reviewed existing signage and collaboratively developed new signage templates and posted signs. The signage was then evaluated using a rapid appraisal questionnaire involving 50 parents and nurse respondents. At each stage of data collection, the matic content analysis was used to analyse data gathered in process meetings and the reflections of participating nurses. Results: A design template and then 44 new signs were developed and used to replace old signage. Respondents reported that the new signs were noticeable, looked attractive and were easily understandable. Conclusion: Intentional and active participation of nurses in clinical paediatric settings ensured collaborative data gathering and analysis. An inclusive research design allowed for insights into the words and tone of posted signs that nurse participants had not noticed previously. The participative redesign of signage resulted in a sense of ownership of the signs.The support and involvement of hospital management throughout ensured that the resulting signage received wide acceptance.